(untitled) (International Journal of Engineering and Computer Science, 2017)
The image processing is the technique which processes the input image and generates required results. In this work, the technique is been proposed which is improvement in intelligent water drops algorithm to detect brain tumor. The MRI images are taken as input which will be given to IWD algorithm for tumor detection. In this work, improvement is been proposed which is based on SVM classifier. The output of IWD algorithm is given as input to SVM classifier which will classify the cancer and non-cancer cells from the MRI images. The proposed and existing techniques is been implemented in MATLAB and it is been analyzed that accuracy of detection is increased upto 20 percent and execution time is reduced to 1.5 seconds